Sodium Iodide: an Alternative Treatment Option for Feline Sporotrichosis? - Carvalho, Beatriz Wanderosck; Pereira, Sandro Antonio; Fernandes Figueiredo, Anna Barretos; de Miranda, Luisa Helena Monteiro; Pereira-Oliveira, Gabriela Reis; Schubach, Tânia Maria Pacheco; Gremião, Isabela Dib Ferreira (Acta Scientiae Veterinariae, 2018)
Background: Sporotrichosis is caused by pathogenic fungi of the genus Sporothrix. The clinically relevant species are S. schenckii, S. globosa and S. brasiliensis. In Brazil, S. brasiliensis is the most prevalent etiological agent among humans and cats. In cats with sporotrichosis, skin lesions are mainly characterized by nodules and ulcers, usually located in the head, nasal region and limbs. The presence of respiratory signs concomitantly with cutaneous lesions is frequent, especially sneezing, and may be associated with lesions located in the nasal mucosa. Ketoconazole (KTZ), itraconazole (ITZ), potassium iodide (KI), sodium iodide (NaI), terbinafine (TRB), fluconazole (FLZ) and amphotericin B (AMB) are the drugs currently available for treating feline sporotrichosis. ITZ remains the drug of choice. ITZ combined with KI has been successfully used in the treatment of naïve cats (especially cases with lesions in the nasal region), cases of recurrence and refractory to ITZ. Clinical cure with NaI has been described in some cases, but its use has been limited by adverse reactions. The conventional formulation is the saturated solution and the recommended dose in the treatment of feline sporotrichosis is 10 mg/kg every 12 h. Cats are sensitive to iodide preparations and should be carefully monitored for clinical evidence of iodism, such as apathy, anorexia, vomiting, diarrhea, hypothermia, hyperthermia, cardiomyopathy, hyperexcitability, muscular spasms and ptyalism. The purpose of this study was to evaluate the therapeutic response of NaI capsules in feline sporotrichosis. Materials, Methods & Results: An observational cohort study was conducted in cats with sporotrichosis at the Laboratory of Clinical Research in Dermatozoonoses in Domestic Animals (Lapclin-Dermzoo), Evandro Chagas National Institute of Infectious Diseases (INI)/Oswaldo Cruz Foundation (Fiocruz), Rio de Janeiro, Brazil. Twenty-eight cats with sporotrichosis confirmed by isolation of Sporothrix spp. in culture, no previous systemic antifungal therapy, and weight above 3.0 kg, were included in the study. The treatment consisted of NaI oral capsules (5 mg/kg/once daily). In cats without clinical improvement after one month of treatment, the dose was increased (10 mg/kg/once daily). The cats were followed up monthly by clinical examination, complete blood count and biochemical analysis (urea, creatinine, alanine aminotransferase - ALT, aspartate aminotransferase - AST, alkaline phosphatase - FA). All procedures were approved by the Animal Ethics Committee (CEUA/Fiocruz), number LW 56/13, and the informed consent term was obtained from all tutors. Clinical cure was achieved in six (21.4%) cases and treatment failure was observed in 13 (46.4%) animals. Seven (25%) cats were lost during follow up, and unknown causes of death occurred in two cases (7.1%). Ten animals (35.7%) presented clinical adverse reactions at some point during treatment. Hyporexia and weight loss were the most frequent ones. Three cats presented alteration in renal function. Discussion: Treatment of feline sporotrichosis in epizootic areas has been a challenge for veterinarians and tutors. Additionally, there are few studies evaluating treatment regimens for this mycosis in animals. In this study, NaI was compounded in capsules, because it is easier to administer when compared to the solution, as previously described for KI. Despite the low cost and the convenient administration of the capsule, NaI presented a low cure rate with the dose used. The study of new pharmaceutical forms and lower doses of low-cost drugs is necessary in a scenario of epizootic sporotrichosis, where investments for the development of new antifungal agents are scarce.